Rindi : an ethnographic study of a traditional domain in eastern Sumba - Forth, Gregory (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1981)
The author describes Rindi culture within an analytic framework that illustrates connexions between, and common principles among, often apparently disparate realms of thought and action. The book contains chapters on the house; the village and the domain (an aggregate of villages); space and cosmos; religion (the notions \'hamangu\' and \'ndewa\'; divinity and the ancestors; the powers of the earth); the cycle of life and death; social order (class stratification; the division of authority; descent groups) and the system of asymmetric prescriptive alliance by which it is governed; marriage prestations and the various ways of contracting a marriage. The study is based on 22 months of fieldwork.